IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS ON FINANCING, PERFORMANCE AND LEADERSHIP IN SHARIA COOPERATIVES: Study of the Prosperous Hope Cooperative of UIN Siber Syekh Nurjati Cirebon - Rosviana, Mohammad Irfan; Aziz, Abdul; Wartoyo, Wartoyo (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to find out the implementation of Islamic business ethics in financing, employee performance and leadership roles in the sharia cooperative of UIN Siber Syekh Nurjati Cirebon. The approach in this study uses a normative qualitative approach. This approach is carried out by focusing on principles that aim to explain the phenomenon in depth regarding the object studied about the implementation of Islamic business ethics in cooperatives of hope for prosperity. Meanwhile, the type of research used is normative qualitative research. This research was conducted in the Harapan Sejahtera cooperative. The data collected in this study are primary data by conducting observations, interviews and documentation. This prosperous hope cooperative implements Islamic business ethics in financing products that are practiced in accordance with the principles of Islamic Business Ethics This is evidenced in its implementation which is in accordance with Islamic business ethics. The Harapan Sejahtera Cooperative always displays Islamic nuances of giving greetings, dressing modestly and performing aurat. The Harapan Sejahtera Cooperative also continues to emphasize the importance of responding to customer complaints and being solution-oriented. The leadership role in Islamic business ethics at the Harapan Sejati cooperative always provides advice and instruction when its employees make mistakes and want to instill Islamic values in each of its workers. In addition, as proof of success in the leadership aspect of the Harapan Sejati Cooperative, it has been awarded as one of the most outstanding cooperatives in West Java. Based on the achievements of the Harapan Sejahtera Cooperative as a form of leadership that is successful in managing and running its leadership management in the business unit sector in the form of Sharia Cooperatives